The “Roots” of Early Homo’s Survival: The role of geophyte underground storage organs in the diet of Homo ergaster occupying the Cradle of Humankind during the middle Pleistocene - Cordeiro, Jeanne (University of the Witwatersrand, Johannesburg, 2024)
This research project explored the seasonal availability of geophyte USOs in the Cradle of Humankind throughout the year with the view of evaluating the energetic and nutritional contributions of USOs in the diet of early Homo. The study adopted an Optimal Foraging Theory and Niche Construction Theory approach to determine whether geophyte USOs in the Cradle could have offered feasible sources of energy and nutrition for Homo ergaster occupying the Cradle during the middle Pleistocene. The nutritional and calorific values were considered in context of the major cognitive and morphological adaptations that define the early Homo lineage, namely encephalisation and bipedalism. The average area required to be searched to achieve a portion of the assumed calorific requirement of H.ergaster, from USOs, was enumerated in this study. The findings support the hypothesis that geophyte USOs contributed to the year-round sustenance of H.ergaster, and may have been more important in the diet of early Homo than traditionally believed.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science, to the Faculty of Science, School of Geography, Archaeology and Environmental Studies, University of the Witwatersrand, Johannesburg, 2024
Keywords: Human evolution; Homo; Cradle of Humankind; Geophytes; Underground storage organs; Diet; UCTD; SDG-9: Industry, innovation and infrastructure; SDG-15: Life on land